The Tsunami Transformation: How Agency For Reconstruction And Rehabilitation [Brr] Convert Disaster Into An Opportunity To Sustainably Develop Tsunami Affected Regions Of Aceh And Nias - Arifin, A. Hadi; Budiarto, Rahmat (Asian Academy of Management (AAM), 2008)
Reconstruction and rehabilitation is urgently needed by Aceh, both in terms of infrastructure and its development of the economic sector. Acehnese need to face this challenge to not only reconstruct the economics of Aceh but also to reconstruct the infrastructure and to build the social life of the Acehnese people. After the tsunami, Acehnese have lost their family member and also their property. It has been three years and the reconstruction for the transformation is still going on. The primary task of transformation projects should be further intensified and the education system, infrastructure, health, social, cultural, and economic development of Acehnese need to be reconstructed. This paper tries to elaborate the political economy related to the acute problems faced by BRR and Aceh Local Government and other agencies in the region.